Physical Activity Plays an Important Role in Body Weight Regulation - Jean-Philippe Chaput; Lars Klingenberg; Mads Rosenkilde; Jo-Anne Gilbert; Angelo Tremblay; Anders Sjödin (Journal of Obesity)
Emerging literature highlights the need to incorporate physical activity into every strategy intended to prevent weight gain as well as to maintain weight loss over time. Furthermore, physical activity should be part of any plan to lose weight. The stimulus of exercise provides valuable metabolic adaptations that improve energy and macronutrient balance regulation. A tight coupling between energy intake and energy expenditure has been documented at high levels of physical exercise, suggesting that exercise may improve appetite control. The regular practice of physical activity has also been reported to reduce the risk of stress-induced weight gain. A more personalized approach is recommended when planning exercise programs in a clinical weight loss setting in order to limit the compensatory changes associated to exercise-induced weight loss. With modern environment promoting overeating and sedentary behavior, there is an urgent need for a concerted action including legislative measures to promote healthy active living in order to curb the current epidemic of chronic diseases.